Economic dependence and unprotected sex: the role of sexual assertiveness among young urban mothers. - Biello, Katie Brooks; Sipsma, Heather L; Ickovics, Jeannette R; Kershaw, Trace (Journal of urban health : bulletin of the New York Academy of Medicine, 2010)
In the USA, sexual intercourse is the leading route of human immunodeficiency virus transmission among women, primarily through their main partner. Because male condom use is not directly under a woman's control, gender inequalities may help shape this sexual risk behavior. To examine this association, data came from follow-up interviews of young, primarily minority, pregnant women enrolled in a prospective, randomized controlled trial. Specifically, we aimed to determine the relationship between economic dependence on a male partner and condom use, and to establish whether this relationship was mediated by sexual assertiveness. Overall, 28% of women reported being economically dependent on a male partner. Young women dependent on a male partner were 1.6 times more likely to report not using a condom at last sex than women not dependent on their partner (95% confidence interval = 1.11-2.32; p = 0.01). Sexual assertiveness mediated the relationship between economic dependence and condom use (Sobel = 2.05, p = 0.04). Coupled with past research, this study supports the premise that sexual behaviors may be rooted in a complex web of social determinants. Addressing gender inequalities in contextual factors may promote healthier decisions within sexual relationships.
Keywords: Adolescent; Adult; Assertiveness; Economics; Female; Humans; Interviews as Topic; Mothers; Object Attachment; United States; Unsafe Sex; Urban Population; Young Adult